2013
DOI: 10.1055/s-0033-1358472
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Decompression Sickness on Vasomotion of Isolated Rat Vessels

Abstract: Several studies have demonstrated that endothelial function is impaired following a dive even without decompression sickness. During this study we determined the effect of decompression sickness on endothelium-dependent and independent vasoreactivity. For this purpose twenty-seven male Sprague-Dawley rats were submitted to a simulated dive up to 1,000 kPa absolute pressure and divided into 3 groups: safe diving without decompression sickness or dives provoking mild or severe sickness. A fourth control group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
(26 reference statements)
1
15
1
Order By: Relevance
“…However, a study on divers showed both endothelium dependent and independent vascular function were altered after a single air scuba dive, and vascular smooth muscle was postulated to be involved 21 . Another study on rats showed that vascular smooth muscle function was progressively impaired with increased decompression stress with no modification of endothelium-dependent vasorelaxation 31 . The different amount and size of bubbles formed, type of vessels and other predisposing factors could offer possible explanation 4 34 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a study on divers showed both endothelium dependent and independent vascular function were altered after a single air scuba dive, and vascular smooth muscle was postulated to be involved 21 . Another study on rats showed that vascular smooth muscle function was progressively impaired with increased decompression stress with no modification of endothelium-dependent vasorelaxation 31 . The different amount and size of bubbles formed, type of vessels and other predisposing factors could offer possible explanation 4 34 .…”
Section: Discussionmentioning
confidence: 98%
“…Because tiny moving microbubbles cannot be detected by current ultrasound techniques, the possibility remains that bubbles could have existed in the arterial system. In human divers, even large venous bubbles do cross to systemic arteries via right-to-left shunts including patent foramen ovale 20 and, although bubble detection was not performed, insults to arterial smooth muscle have been reported in a rat DCS model while endothelial function remained unchanged 31 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial cells are well-described targets for decompression stress and endothelial injury plays an important role in the process of DCS (Lambrechts et al, 2013; Mazur et al, 2014, 2016; Fok et al, 2015; Wang et al, 2015), though the exact mechanism remains unclear. Whether bubbles are the cause or not, endothelial dysfunction is detectable and obvious following most diving exposures (Madden and Laden, 2009; Chrismas et al, 2010; Klinger et al, 2011; Papadopoulou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Treatments and/or risk factors are then typically evaluated by the degree of difference in the proportion of animals that are diagnosed with DCS following decompression. 1 DCS in the rat has been variously defined and diagnostic criteria include survival time, [2][3][4] observable signs such as walking difficulties, 3,[5][6][7][8][9][10][11][12][13][14] paralysis, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] rolling in a rotating cage, 5-9, 12, 13, 15, 16, 20 twitching/convulsions 5-9, 12, 13, 15, 16 and/or respiratory distress 5-7, 9-11, 13, 14, 17-19 .…”
Section: Introductionmentioning
confidence: 99%